PENERAPAN SISTEM INFORMASI KEUANGAN DAERAH SEBAGAI PROSES AKUNTABILITAS PUBLIK (STUDI KASUS KANTOR BADAN PENGELOLA KEUANGAN DAERAH (BPKD) KABUPATEN SIDENRENG RAPPANG) - Fatimah, Fatimah; Indrayani, Indrayani (Universitas Muhammadiyah Parepare, 2019)
This study aims to analyze and find out the implementation of the Regional Financial Information System as a Public Accountability Process in the Local Government Finance Office (LGFO) in Sidenreng Rappang Regency.The method is used of this research is descriptive qualitative as a gradual cyclical process that begins with the identification of the problem or issue to be studied, after observing and knowing the population that is the subject of the study, then sampling is carried out using the Proportionate Stratified Random Sampling method in determining informants who will be interviewed further to dig deeper about the implementation of Regional Financial Information Systems at the Local GovernmentFinance Office of Sidenreng Rappang Regency. The results showed that the implementation of honesty accountability in terms of being open to the public, there is honesty and not violating the rules. Process accountability, have fulfilled the adequacy of accounting information systems, management information systems and administrative procedures. Program accountability, is very helpful in presenting financial reports appropriately and integration between official in the Sidendeng Rappang Regency so that they can create quality programs that support the strategy to achieve the vision, mission and organizational goals. Policy accountability, has been made and in making decisions a head of official already has a sense of responsibility and concern in carrying out policies in the Local Government Finance Office of Sidenreng Rappang Regency.